Hot corrosion behavior of three different zones of linear friction welded Ti‐22Al‐25Nb alloy. Issue 4 (29th November 2018) - Chen, Xi; Xie, Faqin; Ma, Tiejun; Li, Wenya; Wu, Xiangqing
Abstract : Ti‐22Al‐25Nb joint was achieved by using linear friction welding (LFW) technique. The hot corrosion behavior of base metal, weld zone, and thermo‐mechanically affected zone (TMAZ) was investigated at 700 °C in 25% NaCl‐75% Na2 SO4 (wt%) mixed molten salt. In the initial stage, the base metal and joint exhibit similar oxidation resistant ability, and the corrosion products formed on all zones are mainly composed of TiO2, Nb2 O5, and Al2 O3 . The formation of NaNbO3 first occurs in base metal and TMAZ after 50 h, while the weld zone is free of NaNbO3 until 100 h. The development of pitting corrosion in both base metal and TMAZ is caused by the diffusion of sulfur and re‐oxidation of sulfides. After a prolong exposure in molten salts, more serious sulfuration, acid dissolution, and escape of gaseous chlorides occurred in base metal leading to a drastic acceleration of corrosion rate. Abstract : The study explores the hot corrosion behavior of three different zones of linear friction welded Ti‐22Al‐25Nb alloy. The formation of NaNbO3 first occurs in base metal and TMAZ after 50 h, while the weld zone is free of NaNbO3 until 100 h. The development of pitting corrosion in both base metal and TMAZ is caused by the diffusion of sulfur and re‐oxidation of sulfides. After a prolonged exposure in molten salts, more serious sulfuration, acid dissolution, and escape of gaseous chlorides occurred in base metal leading to a drastic acceleration of corrosion rate.